Village Island, de Menil Collection - Adelaide de Menil (1967)
Located at the mouth of Knights Inlet, between the north east coast of Vancouver Island and the mainland, the Mamalilikala band have inhabited this site for centuries. Mimkwamlis was once the largest village on the coast and it is also where the government and First Nations met head to head in the final crushing blow to potlatching. In December 1921 Chief Dan Cranmer hosted a large potlatch that had taken seventeen years of planning and preparation. By having the potlatch at ‚Mimkwamlis, Chief Cranmer hoped to avoid notice, but Indian Agent Halliday knew of it and arrested forty-five people confiscating the cultural treasures associated with the potlatch ceremony. The people were charged with making speeches, dancing and gift-giving, and were taken to Alert Bay where they awaited trial. It would be almost 60 years before the objects were returned to their rightful owners.